The Efficacy of an AI-Powered Chatbot for Improving Conversational Fluency Among Indonesian University Students - Roya Zahir; Razia Khan; Zara Ali; Rustiyana Rustiyana (International Journal of Language and Ubiquitous Learning, 2025)
Background. Developing conversational fluency in English remains a persistent challenge for Indonesian university students, particularly due to limited opportunities for authentic interaction and a strong reliance on form focused classroom instruction. Purpose. This quantitative study aimed to investigate the preferences of Thai This study investigates the efficacy of an AI powered chatbot in improving students’ conversational fluency within an Indonesian higher education context. The research aims to examine how AI mediated conversational interaction influences fluency development and to evaluate students’ perceptions of the chatbot as a learning tool.   Method. Quantitative data were obtained through pre  and post tests measuring speech rate, lexical richness, and utterance smoothness, while qualitative insights were collected through semi structured interviews and reflective journals Results. The findings show a statistically significant improvement in conversational fluency, with notable gains in speech rate and lexical variation. Students reported increased confidence, reduced speaking anxiety, and high levels of engagement during AI assisted practice. Conclusion. The study concludes that AI powered chatbots can serve as an effective supplementary tool for enhancing conversational fluency in EFL contexts, although long term integration requires pedagogical scaffolding and attention to ethical considerations.